Aplikasi Pengukuran Tinggi dan Berat Badan Manusia Menggunakan Morphological Image Processing - Nicky Nicky; Kartika Gunadi; Anita Nathania Purbowo (Universitas Kristen Petra, 2022)
Currently, there are still many measurements of height and weight body human done manually, where someone who wants to measure height and weight they must have a measuring device. This causes difficulties for people who do not have height and weight measuring facilities such as a stature meter to measure height and a scale to measure weight. But with the development of technology, especially in the image processing, this can be made easier. Estimates of human body height and weight can be known through taking pictures with an android smartphone camera, so it can make it easier to measure height and weight without using manual measurement tools.This study uses morphological image processing methods to recognize objects and determine the object's height from the image. To find out the weight of the object using the body surface area (BSA) formula. Both methods are combined into an applications.The results of the study the average accuracy of measuring height using morphological image processing was 98.6%. Meanwhile, the average accuracy of weight measurement using the body surface area formula is 80.7%.